Development and characterization of sweet potato (Ipomoea batatas L.) leaf crackers. - Jance, Mary Pauline A. (2016.)
Sweet potato (Ipomoea batatas L.) leaves, also known as ?talbos ng camote? or ?dahon ng camote? are rich in protein, dietary fiber, iron, vitamin A, vitamin B2 and other minerals. This locally-grown plant has massive potential for processing but is underutilized and oftentimes discarded. This study intended to utilize the sweet potato leaves by incorporating the dried sweet potato leaf powder in the processing of crackers. It had 8.04% moisture content, 1.87% crude fat, 8.53% crude fiber, 24.0% crude protein, 9.87% ash, 55.1% carbohydrates, 0.471 water activity, and 0.230 mg g-1 Fe. Three cracker formulations were developed by incorporating 3%, 5% and 7% dried sweetpotato leaf powder. The formulation with 3% dried sweetpotato leaf powder was the most preferred by the sensory panel and rated ?like very much?. The most preferred formulation (MPF) had 1.76% moisture content, 11.3% crude fat, 0.301% crude fiber, 12.4% crude protein, 2.53% ash, 73.5% carbohydrates, 0.143 water activity, and 0.151 mg g-1 Fe. Except carbohydrate content, all parameters tested and compared with the control by T-Test were not significantly different at P=0.05.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Crackers; Sweet potato; Ipomoea batatas L